Análise qualitativa do conteúdo do curso de estágio e fundamentos de empreendedorismo de centros de treinamento utilizando o software Maxquda - Baluchi, Nazanin; Amin, Hamed Chaharsough; Arayesh, Mohammad Bagher; Vahedi, Marjan (Nuances: estudos sobre Educação, 2020)
The purpose of this study was to analyze the content of internship courses and entrepreneurship fundamentals of applied science education centers in west of Iran. This study is a qualitative research paradigm. The sample was selected from among the agricultural professors of the mentioned universities and the apprenticeship course employers were selected by purposeful sampling with snowball sampling technique. Data were collected through individual interviews and focus group interviews with semi-structured questions. In the process of gathering information, each survey took about 20 to 30 minutes on average. Finally, after interviewing 20 experts, the data collection process was completed. In this study, data were analyzed using traditional (conventional) content analysis using two steps of open and axial coding and 11 MAXQUDA software. Content Analysis of Expert Interviews to Extract 38 Concepts in Open Coding and 5 Axiomatic and Extensive Concepts Including the Effects of Internship Courses and Entrepreneurship Basics, Internship Course Content and Entrepreneurship Basics, Internship Benefits, Internship Problems, and Features Requirements Course instructor led.